2015
DOI: 10.5812/jjm.28057
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibilities of Candida albicans Isolates to Antifungal Agents in Tokat, Turkey

Abstract: Background:Candida albicans is the pathogenic species most commonly isolated from fungal infections. Management of these infections depends on the immune status of the host, severity of disease, and the choice of antifungal drug. In spite of the development of new antifungal drugs, epidemiological studies have shown that resistance to antifungal drugs in C. albicans strains is becoming a serious problem.Objectives:The aim of this study was to evaluate the in vitro susceptibility of C. albicans isolates to keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 39 publications
8
24
0
1
Order By: Relevance
“…The resistance rate of voriconazole in the present study was 3.8% (6.5% intermediate), and in other studies, it was reported to be 2.3% [5], 6% [3, 19], and 14% [9]. …”
Section: Discussionsupporting
confidence: 71%
“…The resistance rate of voriconazole in the present study was 3.8% (6.5% intermediate), and in other studies, it was reported to be 2.3% [5], 6% [3, 19], and 14% [9]. …”
Section: Discussionsupporting
confidence: 71%
“…On the other hand, the caspofungin resistance rate for C. krusei was documented as 12.5% in a multi-center study by Pfaller et al (25). Similarly, some studies reported that the MIC values of echinocandins were higher for C. parapsilosis strains (26,27). In our study, the caspofungin susceptibility rate was 97.5% and resistance was found in only one (2.5%) C. parapsilosis isolate.…”
Section: Discussionsupporting
confidence: 39%
“…The Candida albicans showed sensitivity to Amphotericin B, Fluconazole, Voriconazole. 9 This study bears a good correlation with our study.…”
Section: Discussionsupporting
confidence: 90%